2020
DOI: 10.18203/2319-2003.ijbcp20200724
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions among elderly in-patients with cardiac illness at a tertiary care centre

Abstract: Background: Drug interactions are major cause of concern in hospitalized patients with cardiac illness especially in elderly population. Therefore, the study was conducted to determine the prevalence and pattern of potential drug-drug interactions (pDDI) and risk factors, if any.Methods: It was a prospective observational study involving 75 elderly in-patients with cardiac diseases. IHEC approval was taken before commencement of study and written informed consent was taken from all the study participants. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…8-10 Globally, the prevalence of PDDI ranges from 2.8% to 63.0%, depending on the population under investigation and study settings. 11 Becker et al found that 0.54% of emergency visits, 0.57% of hospital admissions, 0.12% of patients readmitted to the hospital due to possible DDIs, and 4.8% of the elderly admissions to the hospital were due to drug interactions 12 . The DDIs impart a 20-30% incidence of ADRs, which may increase hospital admission or prolong the length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…8-10 Globally, the prevalence of PDDI ranges from 2.8% to 63.0%, depending on the population under investigation and study settings. 11 Becker et al found that 0.54% of emergency visits, 0.57% of hospital admissions, 0.12% of patients readmitted to the hospital due to possible DDIs, and 4.8% of the elderly admissions to the hospital were due to drug interactions 12 . The DDIs impart a 20-30% incidence of ADRs, which may increase hospital admission or prolong the length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%